Dalits in the frame of Exclusion and Inclusion - Dr. K. M. Ziyauddin, (IJRDO - Journal of Social Science and Humanities Research, 2017)
The term social exclusion has been a popular concept in the contemporary scholarship and largely in the domain of sociological and in the studies related to poverty and discrimination. The prominence of the concept of exclusion and inclusion is undoubted due to primary focus in understanding the processes of exclusion not only in finding ways of participation in everyday life but also the way state as a mechanism functions. If French academia attempted to examine social exclusion for the abused, alcoholic, destitute women then the context becomes obvious to be examined but the moment the context changed, there is demand to examine the new context. For instance India as a nation state faces various forms of challenges that has always hindered the process of inclusion in every walk of socio-economic spheres. This paper attempts to examine the case of Dalits in a pocket of the state of Jharkhand where the process of urbanization has not only helped to establish the identity and occupation of Dalits’ more prominently but also new forms of discrimination in a modern city gets established. Social exclusion is the term used to describe what happens when people or areas are excluded from essential services or every day aspects of life that most of us take for granted. Socially excluded people or places can become trapped in a cycle of related problems such as unemployment, poor skills, low incomes, poverty, poor housing, high crime, bad health and family breakdown. The paper does examines such process of exclusion is visible and observed in several new and smart cities with a blurring death of the old forms of discrimination in the life of peoples living at the margin of the society.